EFEKTIVITAS PEMANFAATAN TAMAN KOTA LEMBAH GURAME DI KOTA DEPOK - Fitriandini, Sumaiyah (Jurnal Ilmiah Desain & Konstruksi, 2014)
Green open space is an important part of a structure forming the city. Green open space has the main function as ecological supporting the city also used as open space adder and supporters of the value of the quality of the environment and culture of an area . As an effort to save the function of government land depok city doing the green open space gurame valley become a city park that serves as green open space the public . In this research approach done is through a qualitative approach .The data collected is the data derived derived from a manuscript interview , field notes , personal documents , and other official documents . The preliminary study in doing in the location of the object of research that is on Jalan Gurame Perumnas Depok I, Kecamatan Beji, Kota Depok. On the activities of these things implemented is observing visually about the situation and the condition of the object of study and conduct observation field .To support Processing and analysis of data to support it is also searching and collecting the study of literature. Based on the observation in the field, and an interview and the analysis made by the general a conclusion that Lembah Gurame City Park has not been optimal and effective, it is caused of elements existing facilities and the implementation of the development is not in accordance with planning so users of city parks not be able to use in accordance with its function of the existence of elements and facilities of the garden of the city.                                                                                 Keywords: effectiveness, the utilization, lembah gurame.